Expression of the Synechocystis sp. strain PCC 6803 tRNA(Glu) gene provides tRNA for protein and chlorophyll biosynthesis. - O'Neill, G P (1990)
In the cyanobacterium Synechocystis sp. strain PCC 6803 (Synechocystis 6803) delta-aminolevulinic acid (ALA), the sole precursor for the synthesis of the porphyrin rings of heme and chlorophyll, is formed from glutamate activated by acylation to tRNA(Glu) (G. P. O'Neill, D. M. Peterson, A. Schön, M. W. Chen, and D. Söll, J. Bacteriol. 170:3810-3816, 1988; S. Rieble and S. I. Beale, J. Biol. Chem. 263:8864-8871, 1988). We report here that Synechocystis 6803 possesses a single tRNA(Glu) gene which was transcribed as monomeric precursor tRNA and matured into the two tRNA(Glu) species. They differed in the extent of modification of the first anticodon base, 5-methylaminomethyl-2-thiouridine (O'Neill et al., 1988). The two tRNA species had equivalent capacities to stimulate the tRNA-dependent formation of ALA in Synechocystis 6803 and to provide glutamate for protein biosynthesis in an Escherichia coli-derived translation system. These results are in support of a dual role of tRNA(Glu). The levels of tRNA(Glu) were examined by Northern (RNA) blot analysis of cellular RNA and by aminoacylation assays in cultures of Synechocystis 6803 in which the amount of chlorophyll synthesized was modulated over a 10-fold range by various illumination regimens or by the addition of inhibitors of chlorophyll and ALA biosynthesis. In these cultures, the level of tRNA(Glu) was always a constant fraction of the total tRNA population, suggesting that tRNA(Glu) and chlorophyll levels are regulated independently. In addition, the tRNA(Glu) was always fully aminoacylated in vivo.